Smart Tourism in Action: How DMOs Use Visuals on Social Media to Shape Mexican Destination Marketing - Polymeri, Niki Athina; Meraz Ruiz, Lino; Olague De la Cruz, Jose Trinidad (Investigaciones Turísticas, 2025)
In the increasingly competitive tourism market, Destination Marketing Organizations (DMOs) play a pivotal role in shaping the perception of destinations through visual content shared on social media platforms. However, research has highlighted significant gaps in how DMOs strategically utilize these visual tools to effectively promote destination image. Many DMOs fail to align their social media content with tourist expectations, peak travel seasons, or strategic branding efforts, resulting in underutilized opportunities to influence tourist decision-making processes. This study addresses this gap by analyzing the visual representation strategies employed by DMOs in five major Mexican tourist destinations—Mexico City, Oaxaca, Puebla, Quintana Roo, and Yucatán. By examining a sample of 7,717 photographs shared on Facebook and Instagram, the research seeks to determine the types of visual content used, assess the correlation between posting frequency and seasonal tourist arrivals, and conduct a semiotic analysis of the images to reveal their deeper symbolic meanings. The findings offer practical insights for improving the effectiveness of visual representation in tourism marketing, with a focus on optimizing DMO strategies to better engage potential tourists and enhance destination image